Macromitrium larrainii, a New Species of Macromitrium (Orthotrichaceae, Bryophyta) from New Caledonia - Thouvenot, L.; Yong, K.T. (A.D.A.C., 2015)
The moss Macromitrium larrainii sp. nov. from Mt Panié, the highest summit of New Caledonia, is described and illustrated. This species is characterised by 1) the hairy appearance of branches due to the long aristate leaves arranged irregularly, not spirally, 2) the narrow leaf lamina asymmetrical above, 3) leaf cells consistently smooth, and 4) upper leaf cells irregular in shape and basal ones linear with a straight lumen. Comparison with similar Macromitrium species in neighbouring countries confirms that it is a new species, likely endemic.